2007
DOI: 10.1007/s10452-007-9142-y
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of bacterioplankton abundance and production in the oligotrophic equatorial Indian Ocean

Abstract: Bacterioplankton abundance and production, chlorophyll a (Chl a) concentrations and primary production (PP) were measured from the equatorial Indian Ocean (EIO) during northeast (NEM), southwest (SWM) and spring intermonsoon (SpIM) seasons from 1°N to 5°S along 83°E. The average bacterial abundance was 0.52 ± 0.29, 0.62 ± 0.33 and 0.46 ± 0.19 (· 10 8 cells l -1 ), respectively during NEM, SWM and SpIM in the top 100 m. In the deep waters (200 m and below), the bacterial counts averaged *0.35 ± 0.14 · 10 8 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…Published data on bacterial production in the Indian Ocean are scarce. Leaving out the highly productive Station 7-8, observed rates of bacterial production ranged from 0.12-1.4 mg C m 23 day 21 in the upper 100 m (average 0.38 + 0.33 mg C m 23 day 21 ), which is similar to an average production of 0.39 + 1.13 mg C m 23 day 21 obtained for non-bloom conditions in a recent study in the equatorial Indian Ocean (range: 0.004 to 4.70 mg C m 23 day 21 , Fernandes et al, 2008). The highly elevated bacterial production in the photic zone at Station 7-8 reflected a strong bacterial response to the postphytoplankton bloom conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Published data on bacterial production in the Indian Ocean are scarce. Leaving out the highly productive Station 7-8, observed rates of bacterial production ranged from 0.12-1.4 mg C m 23 day 21 in the upper 100 m (average 0.38 + 0.33 mg C m 23 day 21 ), which is similar to an average production of 0.39 + 1.13 mg C m 23 day 21 obtained for non-bloom conditions in a recent study in the equatorial Indian Ocean (range: 0.004 to 4.70 mg C m 23 day 21 , Fernandes et al, 2008). The highly elevated bacterial production in the photic zone at Station 7-8 reflected a strong bacterial response to the postphytoplankton bloom conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies in the oligotrophic equatorial Indian Ocean have indicated greater contribution of heterotrophic bacterial production to the biological production (Fernandes et al, 2008;Ramaiah et al, 2009). Selective mineralization of POM resulting in preferential removal of nitrogen rich compounds by heterotrophic bacteria is fairly well-known in marine environments (Eadie and Jeffrey, 1973;Harvey et al, 1995;Kolasinski et al, 2012).…”
Section: Tiomentioning
confidence: 98%
“…Previously, researchers characterized the abundance, diversity, and functions of bacteria in the Indian Ocean by isolation of the cultivable species [26,27]. Recently, studies on environmental microbes were performed from water columns and sediments [28][29][30][31][32][33][34]. Wang et al (2016) and Qian et al (2018) provided an extensive depiction of bacteria in their environmental context [28,31].…”
Section: Introductionmentioning
confidence: 99%